Changes in roughness of denture base and reline materials by chemical disinfection or microwave irradiation: Surface roughness of denture base and reline materials - Ana Lucia Machado; Eunice Teresinha Giampaolo; Carlos Eduardo Vergani; Juliana Feltrin de Souza; Janaina Habib Jorge (University of São Paulo, 2011)
OBJECTIVE: The effect of disinfection by immersion in sodium perborate solution and microwave irradiation on surface roughness of one denture base resin (Lucitone 550 -L), 3 hard chairside reline resins (Tokuyama Rebase II-TR, New Truliner-NT, Ufi Gel hard-UH) and 3 resilient reline materials (Trusoft-T; Sofreliner-S, Dentusil-D) was evaluated. MATERIAL AND METHODS: Thirty specimens of each material were made and divided into 3 groups: Control - not disinfected; P - daily disinfection by immersing in sodium perborate solution (3.8%); MW - microwave disinfection (6 min/650 W). Roughness measurements were made after polymerization (baseline) and after 1, 3 and 28 days. Roughness differences relative to the baseline readings were analyzed by Student's t-test (P=0.05). RESULTS: At baseline, Trusoft showed the highest (P<0.001) mean surface roughness (3.54 µm), and its surface roughness was significantly reduced after 28 days of disinfection by immersion in sodium perborate (P=0.013). Roughness measurements of material Trusoft were not performed after microwave disinfection due to the severe alterations on the surface. In the 3 groups evaluated, changes in roughness were significant for materials Ufi Gel hard (from 0.11 to 0.26 µm; P<0.041) and New Truliner (0.19 to 0.76 µm; P<0.019). The roughness of materials Lucitone 550 (0.37 µm), Tokuyama Rebase II (0.37 µm), Sofreliner (0.49 µm) and Dentusil (0.38 µm) remained unaffected (P>0.05). CONCLUSIONS: The roughness of the hard reline materials Ufi Gel hard and New Truliner was adversely affected by microwave disinfection, immersion in water or in sodium perborate. Microwave disinfection caused severe alterations on the surface of the resilient liner Trusoft.